The UF/IFAS Assessment of Nonnative Plants in Florida's Natural Areas: History, Purpose, and Use - Deah Lieurance; S. Luke Flory (EDIS, 2020)
Nonnative invasive plant species pose a significant threat to Florida’s natural areas. The UF/IFAS Assessment of Nonnative Plants in Florida’s Natural Areas uses literature-based risk assessment tools to predict the invasion risk of both nonnative species that occur in the state as well as species proposed for introduction. The UF/IFAS Assessment team has evaluated more than 900 species, including 208 species proposed for introduction or new uses. The team is actively identifying and evaluating potentially problematic nonnative species (and sub-specific or hybrid taxa). Recommendations and supporting information from the UF/IFAS Assessment can be found at http://assessment.ifas.ufl.edu.